Epicardial Adipose Tissue-Derived IL-1β Triggers Postoperative Atrial Fibrillation - Cabaro, Serena; Conte, Maddalena; Moschetta, Donato; Petraglia, Laura; Valerio, Vincenza; Romano, Serena; Di Tolla, Michele Francesco; Campana, Pasquale; Comentale, Giuseppe; Pilato, Emanuele; D’Esposito, Vittoria; Di Mauro, Annabella; et al. (Frontiers in Cell and Developmental Biology, 2022)
Background and aims. Post-operative atrial fibrillation (POAF), defined as new-onset AF in the immediate period after surgery, is associated with poor adverse cardiovascular events and a higher risk of permanent AF. Mechanisms leading to POAF are not completely understood and epicardial adipose tissue (EAT) inflammation could be a potent trigger. Here, we aim at exploring the link between EAT-secreted interleukin (IL)-1β, atrial remodeling, and POAF in a population of coronary artery disease (CAD) patients. Methods. We collected EAT and atrial biopsies from 40 CAD patients undergoing cardiac surgery. Serum samples and EAT-conditioned media were screened for IL-1β and IL-1ra. Atrial fibrosis was evaluated at histology. The potential role of NLRP3 inflammasome activation in promoting fibrosis was explored in vitro by exposing human atrial fibroblasts to IL-1β and IL-18. Results. The 40% of patients developed POAF. Patients with and without POAF were homogeneous for clinical and echocardiographic parameters, including left atrial volume and EAT thickness. POAF was not associated with atrial fibrosis at histology. No significant difference was observed in serum IL-1β and IL-1ra levels between POAF and no-POAF patients. EAT-mediated IL-1β secretion and expression were significantly higher in the POAF group compared to the no-POAF group. The in-vitro study showed that both IL-1β and IL-18 increase fibroblasts’ proliferation and collagen production. Moreover, the stimulated cells perpetuated inflammation and fibrosis by producing IL-1β and transforming growth factor (TGF)-β. Conclusions. EAT could exert a relevant role both in POAF occurrence and in atrial fibrotic remodeling.